Renal complications resulting from SARS-CoV-2 infection in hospitalized COVID-19 persons: scoping review - Lima, Anyele Albuquerque (2022)
Aim: To identify renal complications/sequels resulting from SARS-CoV-2 infection in people with COVID-19; and to describe the age characteristic of the studied population. Methodology: Scoping Review performed in the databases Web of Science, BVS, Cochrane Library, MEDLINE via PubMed, CINAHL, SCOPUS, Embase, LILACS. And in online sites: ProQuest Dissertations and Theses, Gray Literature and Google Scholar. The descriptors used were (comorbidity OR sequel OR complications), (kidney diseases OR glomerular disease OR acute kidney injury OR nephropathy) AND (coronavirus OR SARS-CoV-2 OR COVID-19). Inclusion criteria: articles in portuguese, english and spanish, with different methodological approaches, available in full, online, published from january 1, 2020 to September 29, 2021. And exclusion: people with previous diagnoses of renal pathologies acute and/or chronic; letters to the editor; opinion articles; editorials; and notes. Results: Ten articles were selected, which showed that the infectious process caused by SARS-CoV-2 can start with mild proteinuria and hematuria, and progress to an acute kidney injury caused by the reduction in the glomerular filtration capacity, which favors the retention of some nitrogenous slag, causing increased creatinine and urea levels. Furthermore, they reported that individuals aged between 52-69 years were the most affected. Conclusions: Complications/sequels resulting from SARS-CoV-2 infection are: deposition of immune complexes in renal cells, proteinuria, hematuria, increase in serum creatinine, increase in nitrogenous urea in the blood, decrease in TGF, and AKI stage 1, 2 and 3. These complications have mostly occurred in people aged  ≥ 52 years.